Coffee Shop Liquid Waste Treatment System Using Portable Waste Water Treatment Plant (WWTP) - Ivontianti, Wivina Diah; Rakasiwi, Rinjani Ratih; Sintanggang, Eva Pramuni Oktaviani; Syaifurrahman, Syaifurrahman; Aulia, Penny (Universitas Tanjungpura, 2024)
Coffee shops produce waste that is included in the category of domestic waste in a fairly large amount. Therefore, it is necessary to carry out domestic wastewater management. One solution is the design of an integrated portable WWTP that can treat waste from coffee shop business activities. The advantages of using WWTP are that it is simple and does not require large amounts of land. The processing of this WWTP consists of filtration and precipitation. The wastewater to be filtered will be separated from the solids, after which it will be continued with stratified filtration using activated carbon. In the study, variations in flow rate were carried out to determine processing efficiency, namely variations in tap openings of 30o, 45o, and 90owith water flow rate of 200, 360, and 570 mL/s. The result of research, the portable Wastewater Treatment Plant with activated carbon filtration designed has been able to treat coffee shop liquid waste. The variation of flow rate in the processing of coffee shop liquid waste affects the processing results where the smaller the flow rate, the greater the efficiency reduction. The optimum flow rate variation in this study is 200 mL/s with a COD removal efficiency of 48.5%, TSS 72.8%, Coliform 66.6%, TDS 62.5%, and pH 6.2. The suggestion that can be given is the addition of a biological treatment system to optimize the performance of Portable WWTP.